The linguistic side of ressentiment - Bertollini, Adriano (Rivista Italiana di Filosofia del Linguaggio, 2023)
This article moves from the idea that ressentiment is a characteristic passion of the present time. In what follows, we will try to trace a brief anatomy of it (§§ 1-3) through some classics of literature (philosophical and non-philosophical): Nietzsche’s On the Genealogy of Morality, Scheler’s Das Ressentiment im Aufbau der Moralen, but also Dostoevsky’s Notes from Underground. We will then emphasize (§§ 4-5) the central role played by language and practices of self-narrative. Finally (§ 5), we will try to provide some additional footholds to the initial thesis through an in-depth examination of a typical figure of ressentiment characteristic of our times, the victim, focusing especially on the rhetorical advantages that victim mythology produces.